Association between ondansetron use and symptom persistence in children with concussions: A 5P substudy. Issue 2 (7th June 2018) - Gravel, Jocelyn; Boutis, Kathy; Tang, Ken; Beauchamp, Miriam H.; Freedman, Stephen B.; Dubrovsky, Alexander Sasha; Gagnon, Isabelle; Momoli, Frank; Zemek, Roger
Abstract: Objective: Ondansetron is increasingly administered to children suffering from concussion-associated nausea/vomiting. We examined the association between ondansetron administration and post-concussion symptoms in children at 1 week and 1 month following the concussion. Methods: This was a secondary analysis of data collected prospectively in a cohort study conducted in nine pediatric emergency departments (EDs) (5P study). Participants were children ages between 5 and 17.99 years who sustained a concussion in the previous 48 hours. For the current study, only 5P participants who reported nausea and/or vomiting in the ED were eligible. The exposure of interest was ondansetron administration; the comparison group included all other participants. The primary outcome was an increase in at least three symptoms of the Post-Concussion Symptom Inventory score at 1 week and 1 month following trauma. Results: Among the 3, 063 children included in the 5P study, 1805 (59%) reported nausea and provided data at 1 week and/or 1 month. Among them, 132 (7%) received ondansetron. Multivariable logistic regression adjusted for confounders did not show an association between ondansetron use and the risk of persistent post-concussion symptoms at 1 week (OR: 1.13 [95% CI: 0.86-1.49]), but it was associated with a higher risk at 1 month (OR: 1.33 [95% CI: 1.05-1.97]). Conclusion: In children presenting to the ED with an acute concussion, ondansetron use was associated with a higher risk of persistent post-concussion symptoms at 1 month. Although this may be related to the limitations of the design, it highlights the importance of evaluating this association using a randomized clinical trial. RÉSUMÉ: Objectif: On administre de plus en plus souvent de l'ondansétron aux enfants qui souffrent de nausées ou de vomissements associés à une commotion cérébrale. L'étude visait à examiner l'association entre l'utilisation de l'ondansétron et les symptômes liés à une commotion cérébrale chez les enfants, une semaine et un mois suivant le trauma. Méthode: Il s'agit d'une analyse secondaire de données recueillies dans le cadre d'une étude prospective de cohorte (étude 5P), menée dans 9 services des urgences (SU) pédiatriques. Les participants étaient des enfants âgés de 5 à 17, 99 ans, qui avaient subi une commotion cérébrale au cours des 48 heures précédentes. Seulement les participants de l'étude 5P faisant état de nausées ou de vomissements au SU, étaient admissibles à l'étude en question. Le point d'intérêt était l'administration d'ondansétron; le groupe de comparaison était formé de tous les autres participants. Le principal critère d'évaluation consistait en l'intensification d'au moins 3 symptômes selon l'inventaire des symptômes postcommotionnels, une semaine et un mois suivant le trauma. Résultats: Sur les 3063 enfants ayant participé à l'étude 5P, 1805 (59 %) avaient fait état de nausées ou de vomissements, et avaient fourni des données au bout d'une semaine et d'un mois. Parmi ceux-ci, 132 enfants (7 %) avaient reçu de l'ondansétron. D'après une analyse de régression logistique à plusieurs variables, rajustée pour tenir compte de facteurs parasites, il n'y avait pas d'association entre l'utilisation de l'ondansétron et le risque de persistance de symptômes postcommotionnels au bout d'une semaine (risque relatif approché [RRA] : 1, 13 [IC à 95 % : 0, 86-1, 49]), mais une association a été établie avec une augmentation du risque au bout d'un mois (RRA : 1, 33 [IC à 95 % : 1, 05-1, 97]). Conclusions: D'après les résultats de l'étude, l'utilisation de l'ondansétron chez les enfants traités au SU pour une commotion cérébrale en phase aiguë a été associée à une augmentation du risque de persistance de symptômes postcommotionnels au bout d'un mois. Si les constatations peuvent être liées aux limites du plan d'étude, elles font néanmoins ressortir l'importance d'évaluer la relation dans le cadre d'un essai clinique à répartition aléatoire.